The Novel Application of EUK‐134 in Retinal Degeneration: Preventing Mitochondrial Oxidative Stress‐Triggered Retinal Pigment Epithelial Cell Apoptosis by Suppressing MAPK/p53 Signaling Pathway - Tsou, Shang‐Chun; Chuang, Chen‐Ju; Hsu, Chin‐Lin; Chen, Tzu‐Chun; Yeh, Jui‐Hsuan; Wang, Meilin; Wang, Inga; Chang, Yuan‐Yen; Lin, Hui‐Wen (Environmental toxicology, 2025)
ABSTRACT Age‐related macular degeneration (AMD), a leading cause of blindness, is characterized by mitochondrial dysfunction of retinal pigment epithelium (RPE) cells. EUK‐134 is a mimetic of SOD2 and catalase, widely used for its antioxidant properties in models of light‐induced damage or oxidative stress. However, its effects on the retina are not yet clear. Here, we investigated the capability of EUK‐134 in averting AMD using sodium iodate (NaIO3)‐induced Balb/c mouse and ARPE‐19 cells (adult RPE cell line). In vivo, EUK‐134 effectively antagonized NaIO3‐induced retinal deformation and prevented outer and inner nuclear layer thinning. In addition, it was found that the EUK‐134‐treated group significantly down‐regulated the expression of cleaved caspase‐3 compared with the group treated with NaIO3 alone. Our results found that EUK‐134 notably improved cell viability by preventing mitochondrial ROS accumulation‐induced membrane potential depolarization‐mediated apoptosis in NaIO3‐inducted ARPE‐19 cells. Furthermore, we found that EUK‐134 could inhibit p‐ERK, p‐p38, p‐JNK, p‐p53, Bax, cleaved caspase‐9, cleaved caspase‐3, and cleaved PARP by increasing Bcl‐2 protein expression. Additionally, we employed MAPK pathway inhibitors by SB203580 (a p38 inhibitor), U0126 (an ERK inhibitor), and SP600125 (a JNK inhibitor) to corroborate the aforementioned observation. The results support that EUK‐134 may effectively prevent mitochondrial oxidative stress‐mediated retinal apoptosis in NaIO3‐induced retinopathy.